Using Google Forms as a tool to review and evaluate English grammar knowledge at Hong Bang International University - Tùng, Nguyễn Như; San , Tiêu Bích; Trúc, Trần Thanh; Thảo, Nguyễn Thị Bích; Hương , Trần Thị; Ân, Nhâm Thị Hoàng (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Learning outcomes assessment plays a significant role in teaching and learning, not only does it motivate learners but also provide information about how newly transmitted knowledge has been absorbed by learners. It is obviously true that both teachers and students require to adjust the content, teaching and learning methods to achieve the set goals. Using the Google Forms tool, teachers can easily assess students understanding in English Grammar classes at HIU. This study aims to explore the opinions of HIU students about the Google Form tool in reviewing and testing English Grammar knowledge. The research team used qualitative and quantitative methods to collect data from 94 first-year students of the English Language Department of Hong Bang International University. Specific methods for data collection are observations, interviews, and online surveys. Initial results show that the majority of students have positive comments about this assessment tool such as creating excitement, motivation, ease of use, receiving instant scores and feedback;in addition , students can self-test many times, which helps them memorize the content quickly. However, there are also a few students who believe that this tool is dependent on technology, limited to some types of exercises, and does not comprehensively foster students' creative and application skills.